Praktyczne aspekty zarządzania projektami finansowanymi ze środków Unii Europejskiej - Marciszewska, Anna (Practical aspects of management of the projects financed by European Union Funds, 2007)
The article covers the issue conceming the concept of project management, which constitutes a favourable instrument in gaining financial means from structural funds. The article contains some practical instructions conceming primarily the preparation of the project and transferring project assumptions into petition. Its factual content determines the results of obtaining the EU subsidization. The practical aspects were presented on the basis of the accessible data from the Polish Enterprise Development Agency, published research fmdings in this area, and some personal experiences of the author.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 299-309